2018
DOI: 10.1016/j.tcs.2018.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Vertex deletion problems on chordal graphs

Abstract: Containing many classic optimization problems, the family of vertex deletion problems has an important position in algorithm and complexity study. The celebrated result of Lewis and Yannakakis gives a complete dichotomy of their complexity. It however has nothing to say about the case when the input graph is also special. This paper initiates a systematic study of vertex deletion problems from one subclass of chordal graphs to another. We give polynomial-time algorithms or proofs of NP-completeness for most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…It is also shown that d-claw-vd remains NP-complete when restricted to split graphs of diameter 2 and to bipartite graphs of diameter 3 (with only two vertices of unbounded degree) and polynomially solvable on bipartite graphs of diameter 2, and thus another dichotomy with respect to diameter. We also define a new class of graphs called d-block graphs which generalize the class of block graphs and show that d-claw-vd is solvable in linear time on d-block graphs, extending the algorithm for cluster-vd on block graphs in [5] to d-claw-vd, and improving the algorithm for (unweighted) 3-claw-vd on block graphs in [2] to 3-block graphs. We note that vertex cover and cluster-vd have been considered by a large number of papers in the context of approximation, exact and parameterized algorithms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is also shown that d-claw-vd remains NP-complete when restricted to split graphs of diameter 2 and to bipartite graphs of diameter 3 (with only two vertices of unbounded degree) and polynomially solvable on bipartite graphs of diameter 2, and thus another dichotomy with respect to diameter. We also define a new class of graphs called d-block graphs which generalize the class of block graphs and show that d-claw-vd is solvable in linear time on d-block graphs, extending the algorithm for cluster-vd on block graphs in [5] to d-claw-vd, and improving the algorithm for (unweighted) 3-claw-vd on block graphs in [2] to 3-block graphs. We note that vertex cover and cluster-vd have been considered by a large number of papers in the context of approximation, exact and parameterized algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…When restricted to chordal graphs, it is shown in [2] that 3-claw-vd remains NP-complete even on split graphs. The computational complexity of 2-claw-vd on chordal graphs is still unknown [4,5]. Both 2-claw-vd and 3-claw-vd can be solved in polynomial time on block graphs [2,5], a proper subclass of chordal graphs containing all trees.…”
Section: D-claw-vdmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in the Split to Threshold Vertex Deletion (STVD) problem the input is a split graph G and an integer k, and the goal is to decide whether there is a set S of at most k vertices such that G − S is a threshold graph. The SBVD and STVD problems were shown to be NP-hard by Cao et al [1]. A split graph G is a block graph if and only if G does not contain an induced diamond, where a diamond is a graph with 4 vertices and 5 edges.…”
Section: Introductionmentioning
confidence: 99%